2007
DOI: 10.1681/asn.2006111207
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Treatment during Hemodialysis in a Randomized Trial Improves Nutrition, Quality of Life, and Cardiovascular Risk

Abstract: Nutritional markers, such as lean body mass (LBM) and serum albumin, predict outcome in dialysis patients, in whom protein-energy malnutrition is associated with increased morbidity and mortality. The metabolic effects of human growth hormone (hGH) may improve the nutritional and cardiovascular health of these patients and consequently reduce morbidity and mortality. The aim of this study was to establish clinical proof of concept of hGH treatment for the improvement of the nutritional status in adult patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 45 publications
2
67
0
1
Order By: Relevance
“…In GH-deficient adults, GH replacement therapy is reported to decrease insulin sensitivity during the initial months of treatment with a subsequent reversal toward improved insulin sensitivity thereafter (39). An initial decrease in insulin sensitivity with GH therapy followed by increased sensitivity may be related to a rise in their LBM and a decrease in fat mass, as was observed in the phase 2 study in MHD patients (9). Such a biphasic response may explain the initial rise in fasting plasma glucose that occurred in the GH-treated patients in the phase 2 study (weeks 2 to 4) with a subsequent (week 12 onward) return to baseline glucose levels (9).…”
Section: Safety Aspects Of Ghmentioning
confidence: 86%
See 1 more Smart Citation
“…In GH-deficient adults, GH replacement therapy is reported to decrease insulin sensitivity during the initial months of treatment with a subsequent reversal toward improved insulin sensitivity thereafter (39). An initial decrease in insulin sensitivity with GH therapy followed by increased sensitivity may be related to a rise in their LBM and a decrease in fat mass, as was observed in the phase 2 study in MHD patients (9). Such a biphasic response may explain the initial rise in fasting plasma glucose that occurred in the GH-treated patients in the phase 2 study (weeks 2 to 4) with a subsequent (week 12 onward) return to baseline glucose levels (9).…”
Section: Safety Aspects Of Ghmentioning
confidence: 86%
“…Most of these studies were performed on small numbers of patients. A recent phase 2 RCT involving 139 MHD patients indicated that the GH-treated patients underwent improvement in LBM, serum transferrin, exercise capacity, and a tendency (P ϭ 0.076) for serum albumin to rise (9). Based on these data, a decision was made to conduct a more definitive prospective RCT in hypoalbuminemic MHD patients.…”
mentioning
confidence: 99%
“…Recombinant human growth hormone (rhGH), an approved treatment of short stature in pediatric patients with CKD (60), leads to improved growth, confirming that rhGH could overcome GH resistance associated with CKD. In adults with CKD, resistance to native GH may be responsible for the premature decline in body composition (61). In a large multicenter RCT, C-reactive protein, homocysteine, HDL cholesterol, and transferrin levels significantly improved in hypoalbuminemic patients receiving maintenance HD (62).…”
Section: Treatment Of Pew: An Integrated Approachmentioning
confidence: 98%
“…67, 68 Some small trials suggest that human growth hormone (HGH) may improve fatigue and overall HRQOL in dialysis patientspossible mechanisms being improvement in the nutritional status (lean body mass, albumin) or changes in levels of certain inflammatory mediators (decrease in TNF-α level). 123,124 Intravenous levocarnitine infusion has also been shown to effect fatigue. 75 Psychostimulants such as methylphenidate have shown significant improvement in cancer related fatigue and may be useful in ESRD patients, although evidence supporting this is lacking.…”
Section: Interventions To Reduce Fatiguementioning
confidence: 99%